Are you attracted? Do you remain? Meta-analytic evidence on flexible work practices - Greta Onken-Menke; Stephan Nüesch; Claudia Kröll (Business Research, 2018)
This meta-analysis investigates how three flexible work practices (FWPs), flexible work schedules, telecommuting and sabbaticals, affect organizational attractiveness for job seekers and the organizational attachment of employees. Based on organizational support theory and signalling theory, we conjecture that anticipated organizational support mediates the positive relationship between FWPs and organizational attractiveness. Applying the conservation of resources theory, we suggest that FWPs increase organizational attachment through increased perceived autonomy. Meta-analytic results based on 68 studies and 52,738 employees indicate that FWPs increase organizational attractiveness and that the positive effects are partially mediated by anticipated organizational support. We also find that flexible work schedules and sabbaticals (but not telecommuting) increase organizational commitment and that all FWPs decrease turnover intention. Furthermore, these effects are partially mediated by perceived autonomy. Implications for practice and future research are discussed.
Keywords: 650; Flexible work schedules; Telecommuting; Sabbaticals; Organizational attractiveness; Organizational attachment